2006
DOI: 10.1111/j.1365-2621.2006.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of how phase separation by filtration instead of centrifugation affects protein yield and gel quality during an alkaline solubilisation process – different surimi‐processing methods

Abstract: Filtration and centrifugation for separating functional proteins from an alkaline solubilisation process are investigated. The influence of the method of separation on the yield and the gel quality of surimi produced from the protein isolates was studied. The possibility of replacing centrifugation by filtration is investigated for a first and a second centrifugation step where the first centrifugation separates a dissolved protein phase at high pH from undissolved material and the second centrifugation separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
2
14
0
1
Order By: Relevance
“…The simplest strategy would be just time, i.e., gravity or filtration. Nolsøe et al (2007) found protein yields between 58% and 75% from cod and haddock mince using the alkaline process with centrifugation in the first separation step. When replacing the first centrifugation with sieving, the protein yields obtained were between 82% and 89% of the ground fish muscle.…”
Section: Processing Simplifications and Attempts For Upscalingmentioning
confidence: 98%
“…The simplest strategy would be just time, i.e., gravity or filtration. Nolsøe et al (2007) found protein yields between 58% and 75% from cod and haddock mince using the alkaline process with centrifugation in the first separation step. When replacing the first centrifugation with sieving, the protein yields obtained were between 82% and 89% of the ground fish muscle.…”
Section: Processing Simplifications and Attempts For Upscalingmentioning
confidence: 98%
“…; Nolsøe et al . ), which leads to better protein–protein and protein–water interactions. The best protein–protein interaction is associated with higher values of hardness and gel strength, and the best protein–water interaction may be associated with a higher WHC, as reported in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Fat content of fish protein isolate is usually less than 1%, if a high speed centrifuge is used (Shaviklo, 2007). The higher amount of fat will be found, if filtration is applied to separate soluble and insoluble phases in the pH-shift process (Nolsøe et al, 2007). The moisture content of fish protein isolate depends on dewatering methods, too.…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%
“…The red meats were removed from the fish flesh manually. A localized filtration based pH-shift method based on Nolsøe et al, (2007) work was used for isolating protein from tuna red meat. No cryoprotectants were added to tuna protein isolate (TPI) and it was used immediately for product development.…”
Section: Fish Protein Isolatesmentioning
confidence: 99%